Revealing the Students’ Level of English Interest in Rural Area - Sulastri, Sulastri; Hartati, Elysa ((JELE) Journal Of English Language and Education, 2024)
There is an issue regarding competency level in mastering English in rural areas. The rural community tends to have a low desire for education. This article aims to reveal the level of students’ English interest in the rural area, especially in the Bantul Regency of Yogyakarta. It used a mixed method with questionnaire and interview to collect the data The result showed that the student's level of English interest in the rural area is high (63%). The interview also revealed three important facts; 1) Economic condition did not influence the level of student's interest but parents’ education does, 2) English is difficult for junior high students who have not received this subject in elementary; 3) It is an important subject to students know they can have better future. This research finding is important to make significant changes in developing English competency in rural areas.